Analisis Perbandingan Efisiensi Operasional antara Bank Syariah dan Bank Konvensional - Judi Ichwan; Dewi Safitri; Hendi Fauzi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study analyzes the difference in operational efficiency between Islamic and conventional banks in Indonesia using the BOPO ratio from financial statement data for the period 2017-2022. The results show that the average BOPO of Islamic banks is higher, reflecting lower operational efficiency compared to conventional banks. However, the operational efficiency of Islamic banks shows a significant improvement trend. Factors such as economies of scale, financing risk, and digital technology affect the efficiency of both types of banks. Conventional banks are more efficient due to economies of scale and established infrastructure. This study recommends strengthening technology, cost efficiency, and product innovation to improve the competitiveness of the banking industry in Indonesia.